PENERAPAN MANAJEMEN ARSIP ELEKTRONIK DALAM OPTIMALISASI PENGELOLAAN ARSIP DI PT KREATIVITAS GANESHA SEJAHTERA - Shenda Junetha Pattikawa; Ocky Sundari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the digital era, archives management is evolving with challenges and opportunities. This research evaluates the use of electronic archives for process optimization. Traditional methods often consume time and are vulnerable to physical risks. This study focuses on the application of electronics for archiving. Primary data was obtained from interviews with managers at PT Kreativitas Ganesha Sejahtera. Findings include: (i) Digital archive storage through softcopy and hardcopy (ii) Grouping based on institution and time (iii) Classification of archives based on subject, form, and function (iv) Use of ERMS and EDMS systems (v) Important information technology infrastructure such as power supply, network, and backup systems.